PREVALENCE RATE OF ESBL AMONG ENTEROBACTERIACEAE ISOLATED FROM UTI PATIENTS IN SULAIMANI PROVINCE - Abdalrahman, Azhi Sarbast; Anwar, Khanda Abdullateef (Journal of Sulaimani Medical College, 2025)
Background Extended-Spectrum β-Lactamase are enzymes that provide resistance against third-and fourth generation Cephalosporins and Monobactams, and they are distributed among the Enterobacteriaceae family. Objectives To describe the prevalence of Extended-Spectrum β-Lactamase among Enterobacteriaceae causing urinary tract infections in Sulaimani province. Patients and Methods One hundred bacterial isolates of Enterobacteriaceae from patients with urinary tract infections attending Smart Hospital (inpatients and outpatients). Urine samples were inoculated onto different culture media. Colony morphology, gram staining, and BD Phoenix™ system were used for bacterial identification. Antibiotic profile and Extended-Spectrum β-Lactamase were observed phenotypically by antibiotic profile results, double disk synergy test, and confirmed by combined disk test methods and BD Phoenix™ system. Results Out of one hundred isolates of Enterobacteriaceae, Escherichia coli was the commonest isolate (89), followed by Klebsiella pneumoniae (10) and one isolate of Proteus mirabilis. According to the antibiotic profile, the most effective antibiotic among all three isolates was Imipenem and Nitrofurantoin, while the most resistant antibiotic was Nalidixic acid and third generation Cephalosporin. The prevalence rate of Extended-Spectrum β-Lactamase -producing Enterobacteriaceae was 69% by the screening tests and 48% by the confirmatory tests Conclusion In this study, Extended-Spectrum β-Lactamase prevalence was shown to be at an alarming rate that must be considered. The high priority of public health justifies further investigation to properly establish annual surveillance systems that can aid in selecting an appropriate antibiotic upon ESBL detection.
Keywords: Cephalosporins; ExtendedSpectrum βLactamase; ESBL; Enterobacteriaceae; UTI